Estudo da Reatividade dos íons complexos cis-[Ru(bpy)2(L)(NO)]n+ onde L=imidazol, 1-metilimidazol, tioureia e sulfito - Cândido, Manuela Chaves Loureiro (2011)
We carried out studies of chemical reactivity, electrochemistry and photochemistry of complexes cis-[Ru(bpy)2(L)(NO)](PF6)n, where L = imidazole, 1-methylimidazole, thiourea and sulfite. Were chosen, therefore, two ligands being  donors and two with ligands that act as -recipient and the results indicated that the nature and strength of these ligands directly influence the strength of the back donation between the metal center and coordinated nitric oxide. The infrared spectra showed a characteristic frequency of nitric oxide coordinated as NO+, and there was variation in the observed value of frequency of NO stretching, dependant of the auxiliary ligand. The results indicate that the backbonding between Ru and NO+ is stronger in the complex featuring the sulfite ligand in the coordination sphere, that complex having a minimum value to that specific stretching frequency, when compared to the other complexes. The experimental data corroborate with the Lever parameter values for the ligands, indicating the contribution of them to the electron density of the metal. The cyclic voltammetry performed in aqueous media indicate that the reduction of NO+ species to NO0 is facilitated with the increase of electron density donation from auxiliary ligands to the metallic center. And the differential pulse voltammetry indicates the possibility of the formation of aqueous-complex from a chemical reaction, after coordinated NO+ reduction. This work have shown that the photochemical release of nitric oxide from the light stimulation of complex solutions is consistent, even being possible to determine the species formed as a product of the photolysis and subsequent calculations of quantum yield of NO0 realese. Quantification of nitric oxide release was performed indirectly, using the technique of square wave voltammetry, which was efficient for the purpose. It was also used a selective electrode for free NO0 molecule, confirming that irradiation of NO+ compounds solutions actually cause the release of coordinated nitric oxide (NO+) to its active form in biological environment.